2004
DOI: 10.1210/me.2003-0173
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of the Dual Phenotypic Janus Mutation of ret Cosegregating with Both Multiple Endocrine Neoplasia Type 2 and Hirschsprung’s Disease

Abstract: Gain-of-function mutations of ret receptor tyrosine kinase, the signaling receptor for glial cell line-derived neurotrophic factor, cause sporadic thyroid and adrenal malignancies as well as endocrine cancer syndromes, such as multiple endocrine neoplasia types 2A and 2B (MEN 2A and MEN 2B) and familial medullary thyroid carcinoma. Loss-of-function mutations of ret cause Hirschsprung's disease (HSCR) or colonic aganglionosis. In 20-30% of families with a mutation at residues 609, 611, 618, or 620 of RET, MEN 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…Anderson) and the immunoprecipitates were characterized by Western blotting using specific antibodies for RET. In line with what was found in cell systems, [15][16][17]25 Western blot analysis in Ret C620R homozygous mice showed the prevailing expression of the Ret 140-kd isoform. (Figure 2B).…”
Section: Characterization Of the Ret C620r Micesupporting
confidence: 75%
See 1 more Smart Citation
“…Anderson) and the immunoprecipitates were characterized by Western blotting using specific antibodies for RET. In line with what was found in cell systems, [15][16][17]25 Western blot analysis in Ret C620R homozygous mice showed the prevailing expression of the Ret 140-kd isoform. (Figure 2B).…”
Section: Characterization Of the Ret C620r Micesupporting
confidence: 75%
“…Using cell systems such as NIH3T3 [15][16][17] or MadinDarby canine kidney (MDCK) cells 25 in which diverse RET constructs have been introduced, different groups have demonstrated that the expression of the 160-kd isoform of RET bearing the Cys620 mutation was very low compared with that of wild-type RET, suggesting that this mutation impairs the transport of RET to the plasma membrane. [15][16][17] The 140-kd product is endoglycosidase H-sensitive, suggesting that the 140-kd band corresponds to an incompletely glycosylated precursor of RET present in the endoplasmic reticulum whereas the 160-kd band is the mature RET protein, fully glycosylated and expressed at the cell surface.…”
Section: Characterization Of the Ret C620r Micementioning
confidence: 99%
“…MEN2A mutations such as C634R are responsive to GDNF, whereas Hirschsprung-MEN2A and Hirschsprung-FMTC mutations of RET (e.g. C620R) do not respond to GDNF [65]. Insensitivity to GDNF renders cells more prone to apoptosis, and these features are shared by all Hirschsprung-associated mutations of RET [66].…”
Section: Hirschsprung Combined With Men2mentioning
confidence: 99%
“…Recombinant plasmids carrying RET9-WT (the short isoform of the proto-RET gene), RET51-WT (the long isoform of the proto-RET gene), RET9-C634R (containing an MEN2A causing mutation), and RET9-M918T (containing the main MEN2B causing mutation) are described elsewhere (Arighi et al 2004). Site-directed mutagenesis was performed, using an in vitro oligonucleotide mutagenesis system (QuikChange XL site-directed mutagenesis; Stratagene, La Jolla, CA, USA), on RET9-WT and RET51-WT cDNAs cloned in the eukaryotic expression vector pCDNA3 (Invitrogen), to obtain RET9-K666E, RET51-K666E, RET9-G691S and RET51-G691S constructs.…”
Section: Construction Of the Ret Mutantsmentioning
confidence: 99%